Manajemen Laba, Sales Growth, Good Corporate Governance dan Tax Avoidance - Indry Cahyani, Ni Putu Bella; Noviari, Naniek (E-Jurnal Akuntansi; Vol 33 No 11 (2023), 2023)
Tax avoidance practices carried out by taxpayers (companies) can cause losses to the country and can hinder national development. The research aims to obtain empirical evidence regarding the influence of earnings management, sales growth, and good corporate governance on tax avoidance. The research was conducted at basic industrial and chemical sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period with a sample size of 120 observations determined using a purposive sampling technique. The data analysis technique used is panel data regression analysis with EViews 12 software. The research results show that earnings management and audit committees have a negative effect on tax avoidance and sales growth and independent commissioners have a positive effect on tax avoidance. Institutional ownership and audit quality have no effect on tax avoidance. Keywords: Tax Avoidance; Earnings Management; Sales Growth; Good Corporate Governance